Angiomyolipoma in a Patient with Situs Inversus Totalis: Managing Two Rare Diseases - Jonathan Mayes; Nigel Heaton (Case Reports in Hepatology)
Hepatic angiomyolipoma is an extremely rare benign hamartomatous lesion. Situs inversus totalis is a genetic condition occurring in 0.01% of the population. Following the kidney, the liver is the second most common site of angiomyolipoma. No consensus on the treatment of hepatic angiomyolipoma has been reached. However, the majority of these tumours are managed conservatively. Situs inversus totalis presents difficulties for procedures and is most commonly an incidental finding. These two conditions have not previously been reported and no genetic link has been established between them. This paper reports the association of both conditions in a 74-year-old female, reviews the literature, and presents CT imaging of the case.